The Contribution Of Food Sector Cooperatives To Food Security And The Free Nutritious Meals Program: A Case Study Of The UPI Melati Mekar Jaya SME Center Producers’ Cooperative, North Bengkulu - Kresnawati Kresnawati; Metriko Haderian; Yenisrida Yenisrida; Putra Pernales; Pedi Herwanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The national priority programs on food security and the Free Nutritious Meals (MBG) initiative require the active participation of cooperatives and food-sector SMEs. This study aims to analyze the contribution of the UPI Melati Mekar Jaya IKM Producer Cooperative in North Bengkulu Regency in supporting food security and the MBG program. Method: A quantitative descriptive approach with a single case study design using 56 monthly transactions of actual sales report data from November 2025 to April 2026. Analysis was conducted using the FAO’s four pillars of food security framework, SWOT analysis, and a Fishbone diagram. Results: Total sales over six months reached Rp411,869,400, with animal protein products accounting for 72.3%. Sales trends were fluctuating (CAGR 18.2%; coefficient of variation 38.5%). The SWOT analysis indicates a Quadrant I position (aggressive strategy) with an IFAS score of 3.38 and an EFAS score of 3.19. Three of the four FAO pillars are met, but the stability pillar remains weak. Four main gaps were identified: production capacity, food safety and nutrition standardization, access to financing, and institutional coordination. Conclusion: Cooperatives possess real capacity as strategic partners of the government, but require strengthening of production capacity and access to capital. Novelty: This study presents empirical evidence based on six months of real transaction data, mapping of the supply chain to SPPGs, and explicit identification of implementation gaps.